2022
DOI: 10.1039/d1np00038a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationship of terpenoid glycosyltransferases from plants

Abstract: The spatial size of the catalytic centre and a large hydrophobic pocket in the active site affect the enzymatic activity and substrate preference of uridine diphosphate–sugar-dependent terpenoid glycosyltransferases in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 193 publications
1
35
1
Order By: Relevance
“…A large number of GT genes have been obtained by using the above gene mining methods, however, there are still some challenges in narrowing down the scope of target GTs mining for specific PNPs glycosylation owing to the labor-intensive function characterization of individual enzymes [ 20 ]. Therefore, development of efficient and flexible enzyme function detection methods is crucial for obtaining comprehensive enzyme functional data.…”
Section: Mining Gts For Biosynthesis Of Glycosylated Pnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of GT genes have been obtained by using the above gene mining methods, however, there are still some challenges in narrowing down the scope of target GTs mining for specific PNPs glycosylation owing to the labor-intensive function characterization of individual enzymes [ 20 ]. Therefore, development of efficient and flexible enzyme function detection methods is crucial for obtaining comprehensive enzyme functional data.…”
Section: Mining Gts For Biosynthesis Of Glycosylated Pnpsmentioning
confidence: 99%
“…Recently, the structure-function relationship and glycosylation mechanisms of terpenoid GTs were summarized [ 3 , 20 ]. The evolution and substrates coverage of GT1 family were also overviewed to pave the way for the future exploration of GT proteins [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though crystal structures had been reported for UGT71G1 (a triterpene/ flavonoid GT from Medicago truncatula) and UGT74AC1 (a triterpene GT from Siraitia grosvenorii), very few studies successfully engineered the protein function. [22][23][24] The structures indicated that the substrate was accommodated by a tunnel formed by hydrophobic amino acids. In addition, the hydrophobic interaction between enzyme and triterpenes plays an important role in anchoring the substrate at the active center to accomplish the glycosylation, which is important for protein engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hydrophobic interaction between enzyme and triterpenes plays an important role in anchoring the substrate at the active center to accomplish the glycosylation, which is important for protein engineering. [24] Recently, a large mutant library (~5000 mutants) based on error-prone PCR and alanine-scanning was built to improve the 3-O-glucosylation efficiency of UGT74AC1 toward mogrol by 41 700fold. [23] Similarly, after screening from ~2800 clones, the 3-O-glucosylation catalytic activity of UGT51 (from S. cerevisiae) toward protopanaxadiol was increased by 610fold.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation is a widespread type of chemical conjugation performed on small molecules in natural product biosynthesis and metabolite detoxification. , Attachment of sugar residue(s) increases the solubility, often defines the bioactivity, and directs the cellular targeting of the metabolite. , In biology, the task of glycosylation is handled by a class of sugar nucleotide-dependent glycosyltransferases. , These enzymes use sugar nucleotides as donors for glycosyl transfer to acceptors. , Glycosyltransferases offer precise α/β stereocontrol of the glycosylation but differ widely in their substrate scope. For example, detoxifying glycosyltransferases are often highly permissive regarding the acceptor substrates used. , Assayed in vitro , some glycosyltransferases of secondary metabolism can use a large diversity of donor and acceptor substrates. , Due to the interplay of different glycosyltransferases in biosynthesis, the glycosylation on small molecules can give rise to considerable structural diversity. , Products can be glycosylated at multiple positions, exhibit a disaccharide, or even an oligosaccharide, attached to the aglycone, or feature both modifications at the same time. , Among the natural products, many (e.g., antibiotics like vancomycin; , flavonoids like quercetin or luteolin; , fragrances and flavors like geraniol ,, ) are found in different glycoside forms and show modulation in function or potency due to change in glycosylation pattern. The steviol glycosides imparting intense sweetness to extracts of the Stevia plant are bis -glycosides, with a disaccharide (stevioside) or trisaccharide (rebaudioside A) attached to the diterpene aglycone. , Our interest here was on metabolite glycosylation with a disaccharide unit, which is chemically challenging to install and not well explored for glycoside synthesis.…”
Section: Introductionmentioning
confidence: 99%